(untitled) (Quinto Sol, 2022)
This article analyzes legislative projects on prison reform presented to the Chamber of Deputies during the first presidencies of the radical party (1916-1930). The multiplicity of initiatives carried out by deputies of different political backgrounds to reorganize the prison system showed how institutions of punishment should be addressed. The context in which these projects were framed, the problems they sought to solve, their specificities, as well as the coincidences and differences they presented is reconstructed through the article. In this way, the importance of Parliament in the prison reform process in Argentina is highlighted.